IMPACT OF DAIRY ALCOHOL HABIT TO HEALTH FACTORS IN JAPANESE SENIORS - MARUI, Akemi; ISHIKAWA, Yumiko; KANEKO, Shoko (LIFE: International Journal of Health and Life-Sciences, 2019)
Objectives: Drunk frequency of senior vary greatly by generation and culture. The objective of the study is to clarify the rate of daily drinker and impact of daily drinking to their health and social characteristics. Methods: A cross-sectional study of community dwelling older people in Japan. Results: The average age of participants was 71.7 years old, ranged from 60 to 90 years old. According to the questionnaire answers, 23.3% of them were drinking as daily routine. People who drink alcohol everyday are reported to be healthy, live with spouse, having work or live actively, and also have a good sleep quality, from the previous studies. On the other hand, depression trend is common among the people who do not drink alcohol every day. Conclusion: This study gave us an information of daily alcohol habit impacts to health factors (e.g. mental factors). In the future work, we should consider quantitatively impacts including harmful revel of alcohol intake and frequency.